Study of Associated Genetic Variants in Indian Subjects Reveals the Basis of Ethnicity Related Differences in Susceptibility to Venous Thromboembolism. (29th September 2014) - Kumari, Babita; Srivastava, Swati; Chatterjee, Tathagat; Vardhan, Rig; Tyagi, Tarun; Gupta, Neha; Sahu, Anita; Chandra, Khem; Ashraf, Mohammad Zahid
Abstract : The genetic variants linked with the susceptibility of individuals to VTE are well known; however, the studies explaining the ethnicity based difference in susceptibility to VTE are limited. Present study assesses mutations in six candidate genes contributing to the etiology of VTE in Indian subjects. The study comprised 93 VTE patients and 102 healthy controls. A PCR-RFLP based analysis was performed for nine mutations in the following genes associated with VTE: favtor V Leiden (FVL), prothrombin, tissue factor pathway inhibitor (TFPI), fibrinogen-beta, plasminogen activator inhibitor 1 (PAI-1), and methylene tetrahydrofolatereductase (MTHFR). All the subjects were found to be monomorphic for FVL 1691G/A, prothrombin 20210G/A and TFPI −536C/T mutations. The mutation in the MTHFR gene (677C/T) was observed only in patients. Contrarily, higher frequency of mutation in the PAI-1 −844G/A and the fibrinogen- β −455G/A was observed in controls in comparison to the patients. This study suggests that the PAI-1 −844G/A and fibrinogen- β −455G/A could be protective variants against VTE in Indians. While MTHFR 677C/T mutation was found to be associated, in contrast to other populations, the established genetic variants FVL 1691G/A, prothrombin 20210G/A, and TFPI −536C/T may not be associated with VTE in Indians thus revealing the basis of ethnicity related differences in susceptibility of Indians to VTE.